The Traces of Franco’s ideology in the usage of Masonic Signs Online: Some photographs of Spain’s II Republic politicians - Hottinger Craig, Sylvia (2018)
We have chosen four signs that are deemed to be Masonic online. In a comparative visual study, we have selected drawings of four masonic signs used as a source by conspiracy theorists. We then contrasted them with authentic photographs from the masonic archives of Salamanca, the Centro de Documentacion de la Memoria Histórica in which the use of the signs is depicted. To finally compare the authentic photographs with the uploaded press photographs of politicians from the 1930’s in Spain since many of the latter were renown Freemasons. In this paper we identify the masonic politicians who could have possibly used these signs in press photographs and in which context these were uploaded and are being used at present.